Validation visit to Muscat College - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
After a year of the academic collaboration commencement, UMP organized its first validation visit to Muscat College of Oman between 2nd and 06th of April 2016. The visit was organized by External Collaboration Unit, Academic Management Division - UMP, Centre for Academic Excellence (CAIC), Faculty of Industrial Management (FIM) and Faculty of Computer Science and Software Engineering (FSKKP). Both the faculties were represented by Deputy Dean of Academic Affairs and CAIC was represented by its Director, Dr Mohd Ruslim Bin Mohammed.